Effect of age on survival in patients undergoing resection of hepatocellular carcinoma. Issue 2 (10th December 2015) - Cucchetti, A; Sposito, C; Pinna, A D; Citterio, D; Ercolani, G; Flores, M; Cescon, M; Mazzaferro, V
Abstract: Background: The benefit of surgical intervention for cancer should be estimated in relation to the life expectancy of the general population. The aim of this study was to provide a measure of relative survival after hepatectomy for hepatocellular carcinoma (HCC). Methods: Consecutive patients with liver cirrhosis and HCC who underwent hepatectomy were divided into age quartiles for analysis. Short- and mid-term survival rates were used to estimate survival until death for all patients, in relation to age and other co-variables. Years of life lost (YLL) were estimated using a reference cohort, derived from the general population matched for sex, age and year of diagnosis. Results: Some 919 patients were included in the study. The following age quartiles were identified: less than 60 years (229 patients), 60–66 years (230), 67–70 years (231) and over 70 years (229). Postoperative mortality rates were similar between age quartiles, as were survival rates up to 3 years ( P = 0·404). A statistically significant reduction in 5–10-year survival rates was observed with ageing ( P = 0·001). Relative survival calculation showed that the youngest age quartile (less than 60 years) experienced the longest entire postoperative lifespan (15·6 years) but also the greatest number of YLL (11·0 years). Patients aged over 70 years had the shortest entire postoperative lifespan (6·4 years) but also the smallest number of YLL (3·7 years). Conclusion: Although survival after liver resection for HCC is shortest in elderly patients, relative survival estimates suggest that hepatectomy can be of benefit in these patients, with a small loss of the entire individual lifespan. Abstract : Hepatectomy for HCC of benefit in elderly